Correlation between the matrix metalloproteinase-9 activity and chondroitin sulfate concentrations in tear fluid after laser in situ keratomileusis - Tetsuya Mutoh (Dove Medical Press, 2010)
Tetsuya Mutoh, Masaya Nishio, Yukihiro Matsumoto, Kiyomi Arai Department of Ophthalmology, Dokkyo Medical University Koshigaya Hospital, Koshigaya, Saitama, JapanAims: The aim of the present study was to evaluate the correlation between matrix metalloproteinase-9 (MMP-9) and chondroitin sulfate (CS) concentrations in human tear fluid following laser in situ keratomileusis (LASIK).Methods: Twelve eyes from six patients who had no ocular complaints except for refractive errors, and who had undergone LASIK, were enrolled in this study. We measured the concentrations of chondroitin 4 sulfate (C4S), chondroitin 6 sulfate (C6S), and MMP-9 activity with an enzyme-linked immunosorbent assay and an enzyme immunocapture activity assay preoperatively and postoperatively on days 1 and 4, week 1, and at 1 and 3 months.Results: Although the preoperative MMP-9 activity and the C4S concentration were highly correlated (r = 0.900; P < 0.001), they were not postoperatively correlated at month 1. Although the preoperative MMP-9 activity and the C6S concentration were highly correlated (r = 0.885; P < 0.001), they were not postoperatively correlated at either week 1 or months 1 and 3.Conclusions: The correlation appeared to be collapsed by LASIK, and it did not recover to the preoperative score at 3 months post-surgery. Our study indicates that the corneal wound healing was not terminated at 3 months following LASIK.Keywords: preoperative correlation, postoperative correlation, wound healing, refractive errors, human cornea